2020
DOI: 10.3390/ijerph17145054
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of Water Quality and Pollution Source Apportionment in Wuliangsuhai Lake, Inner Mongolia, China

Abstract: Water quality is a key indicator of human health. Wuliangsuhai Lake plays an important role in maintaining the ecological balance of the region, protecting the local species diversity and maintaining agricultural development. However, it is also facing a greater risk of water quality deterioration. The 24 water quality factors that this study focused on were analyzed in water samples collected during the irrigation period and non-irrigation period from 19 different sites in Wuliangsuhai Lake, Inner Mongolia, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Several studies around the world have applied PCA to evaluate and classify water quality for irrigation purposes, including China [112], Turkey [113], Nigeria [114], and Brazil [115]. China applied PCA to the Tongjiyan irrigation area, and the given study indicated that the PCA classification had similar results with other methods such as fuzzy evaluation, the Nemerow index, and improved Nemerow index methods.…”
Section: Discussionmentioning
confidence: 90%
“…Several studies around the world have applied PCA to evaluate and classify water quality for irrigation purposes, including China [112], Turkey [113], Nigeria [114], and Brazil [115]. China applied PCA to the Tongjiyan irrigation area, and the given study indicated that the PCA classification had similar results with other methods such as fuzzy evaluation, the Nemerow index, and improved Nemerow index methods.…”
Section: Discussionmentioning
confidence: 90%
“…Despite this situation, the comprehensive pollution index values obtained in ALM were low in comparison to other studies such as the report by Tibebe et al [ 39 ], who obtained values from 0.68 to 0.98 for Lake Tana in Ethiopia. Using this index, Shi et al [ 40 ] and Zhao et al [ 41 ] demonstrated contamination of Lake Wuliangsuhai and Lake Baiyangdian, respectively. Shi et al [ 40 ] discovered that the drainage of agricultural lands was the main source of pollutants in Wuliangsuhai Lake, China.…”
Section: Resultsmentioning
confidence: 99%
“…Using this index, Shi et al [ 40 ] and Zhao et al [ 41 ] demonstrated contamination of Lake Wuliangsuhai and Lake Baiyangdian, respectively. Shi et al [ 40 ] discovered that the drainage of agricultural lands was the main source of pollutants in Wuliangsuhai Lake, China. They also report that the water quality is highly influenced by effluents from diffuse sources and by the many tourist attractions around the Lake.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations